In the shadow of the Mongol Empire Ming China and Eurasia - Robinson, David M. 1965- (Cambridge University Press, 2019)
During the thirteenth century, the Mongols created the greatest empire in human history. Genghis Khan and his successors brought death and destruction to Eurasia. They obliterated infrastructure, devastated cities, and exterminated peoples. They also created courts in China, Persia, and southern Russia, famed throughout the world as centers of wealth, learning, power, religion, and lavish spectacle. The great Mongol houses established standards by which future rulers in Eurasia would measure themselves for centuries. In this ambitious study, David M. Robinson traces how in the late fourteenth century the newly established Ming dynasty (1368-1644) in China crafted a narrative of the fallen Mongol empire. To shape the perceptions and actions of audiences at home and abroad, the Ming court tailored its narrative of the Mongols to prove that it was the rightful successor to the Mongol empire. This is a story of how politicians exploit historical memory for their own gain
Eurasia in Empire's wake -- Daidu's fall -- Changing fortunes -- Black city -- Telling stories and selling rulership -- Precarious tale -- Letters to the Great Khan -- South of the clouds -- Chinggisid fold -- Eastern neighbors
Keywords: Ming Taizu -- China, Kaiser -- 1328-1398; Geschichte 1368-1398; Mongols / History / To 1500; Mongols / China / Historiography; Mongols / Eurasia / Historiography; Historiography / China; Yuandynastie; Kollektives Gedächtnis; Mingdynastie; Mongolen -- Motiv; Geschichtsschreibung; Mongolen; China / History / Ming dynasty, 1368-1644; China